FORMULASI, IMPLEMENTASI DAN EVALUASI STRATEGI DALAM PENYUSUNAN BUSINESS PLAN PADA PT. BOSOWA PROPERTINDO - Ridwan Ridwan; Yuli Yuli (Jurnal Bisnis dan Kewirausahaan, 2018)
The study found that the business strategy is a series of commitments and integrated and coordinated actions designed to gain a competitive advantage by exploring the competence of a single product market or individual products and specific. Formulation of the strategies implemented in several stages,Economi outlook, business target and a draft business plan. The purpose of this study is : (1) to determine the strategy formulation in the preparation of the business plan at PT. BosoowaPropertindo, (2) to know the implementation of strategies to achieve business plan on PT.BosowaPropertindo, and (3) Determining the evaluation of strategies to assess the achievement of the business plan at PT. Bosowa Propertindo. The study used descriptive qualitative method. Data analysis techniques in this research is descriptive. implementation strategy at PT.BosowaPropertindo guarded closely by the office of strategy management division by way of monitoring through periodic meeting in this meeting using the form problem identification and effective corrective action to ensure that the strategy has been implemented correctly